2007
DOI: 10.1103/physreva.75.063813
|View full text |Cite
|
Sign up to set email alerts
|

Extremal transmission at the Dirac point of a photonic band structure

Abstract: We calculate the effect of a Dirac point ͑a conical singularity in the band structure͒ on the transmission of monochromatic radiation through a photonic crystal. The transmission as a function of frequency has an extremum near the Dirac point, depending on the transparencies of the interfaces with free space. The extremal transmission T 0 = ⌫ 0 W / L is inversely proportional to the longitudinal dimension L of the crystal ͑for L larger than the lattice constant and smaller than the transverse dimension W͒. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
231
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(244 citation statements)
references
References 12 publications
8
231
1
1
Order By: Relevance
“…The authors of Ref. [52] have shown that the transmission through this crystal displays a pseudodiffusive [24] 1/L dependence on the thickness L of the crystal. In addition, they measured the eigenmode intensity distributions in a rectangular microwave billiard that contains a triangular photonic crystal.…”
Section: Confining Photonsmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors of Ref. [52] have shown that the transmission through this crystal displays a pseudodiffusive [24] 1/L dependence on the thickness L of the crystal. In addition, they measured the eigenmode intensity distributions in a rectangular microwave billiard that contains a triangular photonic crystal.…”
Section: Confining Photonsmentioning
confidence: 94%
“…In such crystals, the unusual transmission properties near a Dirac point [23][24][25] were predicted and observed experimentally.…”
Section: Confining Photonsmentioning
confidence: 95%
See 1 more Smart Citation
“…When a conical dispersion is restricted to a finite system, the intersection is replaced by a (small) band gap, due to the vanishing density of states. In contrast to regular Bragg gaps, the wave transmission T ∼ 1/L scales pseudo-diffusively with the lattice size L, for both "fermionic" and "bosonic" intersections [18,[77][78][79]. On the other hand, the reflected beam is sensitive to the type of intersection, displaying a suppression of coherent backscattering (weak antilocalization) due to the π Berry phase of "fermionic" intersections [80].…”
Section: Applicationsmentioning
confidence: 99%
“…Photonic crystals have been studied extensively for their bandgap 1 and special in-band dispersion effects such as negative refraction 13 . However, another really interesting feature of photonic crystals is the Dirac points that appear at corners of the Brillouin zone [14][15][16][17] . A Dirac point, as illustrated in Figure 1, is a conical singularity surrounded by a region of linear dispersion in the band structure of triangular, hexagonal, or kagome lattices.…”
Section: Introductionmentioning
confidence: 99%